Etimologia estoica, princípios e propósitos: análise de testemunhos de Cícero e de Laércio - Lopes, Jaynnoã Fernando Silva (2021)
It is the objective of this work to identify, based on testimonies of Cicero and Diogenes Laërtius, the principles and the the purposes of the use of the etymology in the Stoic doctrine, analyzing two of its occurrences based on the philosophical concepts of this particular school. It will be used both the speech of Balbus in the second book of Cicero’s On the Nature of Gods (De Nat.), and also the testimony of Diogenes Laërtius about the Stoics in his Lives of the Eminent Philosophers (Vitae Philos.). In both excerpts, are used etymologies of gods’ names with the objective to demonstrate the theological sentences from this particular school. To distinguish the manner the Stoical advanced in the etymological approach of the words, it was also made necessary to analyze the same approach made before the Hellenistic Period. For this, the first section will present the use of etymology in the Greek writers who chronologically preceded the Stoics, grouping them into two phases: that of poetic etymology – comprising from Homer to the tragediographers – and that of philosophical etymology, since Plato. Considering all this, we are searching to offer a contribution to the studies of the History of Grammar, from which the etymology was part of in Ancient Times. On the other hand, it will be necessary to explore the aspects of the Stoic doctrine that will help in the understanding of its use of etymology, in order to emphasize the physical and logical conceptions that are involved in it; this will be dealt with in the second section. Finally, a translation and an analysis of De Nat. II, 63-71, and of Vitae Philos. VII, 147, are proposed in the last section.